Assessment of Critical Infrastructure Elements in Transport. (2017) - Dvořák, Zdeněk; Sventeková, Eva; Řehák, David; Čekerevac, Zoran
Abstract: The paper describes the long process of developing the transport system of risk assessment models. Researchers in Central European countries many years solved the risk assessment models which are based on the accident scenarios. Purpose and objectives realized research directed at finding the dependencies between the state of transport infrastructure and its potential threat. Various hazardous events, which have the potential to lead to casualties probably, were defined by gathering various accident reports and having conferences and workshops with transport safety and security experts. The developed models will be used to assess the accident risk of the road and railway systems. The frequency of each hazardous event was evaluated from the historical accident data and structured expert Judgments by using the technique FTA, ETA technique and other suitable methods were applied. Research results have shown the need to return more new measures in the response to new sources of risk.